Imaging Bone Metastases: Research Progress - Peiqi WANG; Bin YANG; Zefei PENG; Caiqiong WANG; Jialei WU; Yingchun LIU; Yubo WANG (CT Lilun yu yingyong yanjiu)
Bone is a common site for cancer metastasis, with a higher incidence than primary bone malignancies. As various cancer treatment regimens continue to improve, the five-year survival rate for cancer patients has risen steadily. However, this has also led to an increased likelihood of bone metastasis and skeletal-related events. Timely and accurate diagnosis of bone metastases, along with proper assessment of therapeutic response, is crucial for developing personalized treatment plans and improving patient survival. This paper reviews current imaging examinations for bone metastases, and explores the potential of new imaging techniques for diagnosing tumor-related bone metastases.